Distribution of Extreme Vital Signs and Complete Blood Count Values of Healthy Parturients: A Retrospective Database Analysis and Review of the Literature. (December 2019) - Gat, Roi; Hadar, Eran; Orbach-Zinger, Sharon; Shochat, Tzippy; Kushnir, Shiri; Einav, Sharon
Abstract : BACKGROUND: The impact of physiological adjustments throughout pregnancy on maternal vital signs and laboratory values has yet to be fully defined. The present study was designed to determine the normal range of these parameters among healthy pregnant women during the peripartum period. METHODS: This is a retrospective analysis of data collected during real-time deliveries in a single medical center. Vital signs and laboratory results from the 24 hours preceding delivery room admission and up to 72 hours postpartum were collected. Only pregnant women at term (37 0/7 to 41 6/7 weeks' gestation) with a liveborn, singleton gestation, and no chronic disease or obstetric complication that could affect the physiological parameters under study were included. The mean, range, and standard deviations of the extremes of all parameters at 3 distinct time points (prelabor, intrapartum, and postpartum) were calculated. The 2.5 and 97.5 percentiles for each parameter were reported as the normal range. RESULTS: A total of 32, 161 cases fulfilled inclusion criteria. The average gestational age at delivery was 39 3/7 weeks ± 8 days, and one-third of the cases were primiparous. During labor and after delivery, the upper limits of normal blood pressure values were 147/94 and 145/94 mm Hg, respectively. The lower limits were 83/43 and 83/42 mm Hg, respectively. Normal heart rates were 60–115 beats/min prelabor, 51–120 beats/min intrapartum, and 50–120 beats/min postpartum. Lowest normal temperatures ranged between 36.0°C and 36.3°C in the 3 study time points, and highest normal temperatures were 37.2°C prelabor and 37.6°C intra- and postpartum. The normal ranges of white blood cell counts were 6.1–16.8 prelabor, 6.5–22.5 intrapartum, and 6.4–23.9 K/µL postpartum. Normal low values of hemoglobin were 9.7, 8.7, and 7.1 g/dL and of platelets were 117, 113, and 105 K/µL, respectively. CONCLUSIONS: Our findings justify the practice of using ≥2 repeated measurements for diagnosing hypertensive disorders of pregnancy. Lower normal blood pressure limits may be below those defining hypotensive shock. Normal heart rates exceed the accepted definitions of both tachy- and bradycardia. Normal temperatures at all times have a more narrow range than previously thought, and the normal range of white blood cell count has outliers exceeding the current definitions of leukocytosis or leukopenia at all times. The normal lower range of hemoglobin was constantly below 10 g/dL, and normal platelet counts were considerably lower than those previously described. The vital signs and complete blood count values thus far considered normal for the peripartum period may require some adjustment. New definitions for hypotension, tachy- and bradycardia, fever, and leukocyte quantitative disorders should be considered.